Penerapan telehealth pada gangguan psikologis pasien perioperatif: a literature review - Platini, Hesti; Arisunyoto, Wisnu; Maulana, Indra; Pebrianti, Sandra (JOURNAL OF Mental Health Concerns, 2025)
Background: Patients undergoing surgery often experience stress and anxiety, which can increase complications and hinder recovery. Effective management of psychological factors is key to improving outcomes. Preoperative anxiety is inversely correlated with the amount of information patients receive, but easily accessible personalized support is limited. Purpose: To determine the existing evidence regarding the practice of telehealth, especially telenursing in perioperative patients. Methode: A literature review with a rapid review approach. The strategy in this literature review is with PCC which is used to develop guiding questions: Population (P): surgical patients; Concept (C): telehealth; Context (C): outcomes in the peri-operative period. The study search was conducted with 3 databases namely Pubmed, EBSCO, Proquest and Google Scholar Search Engine. Result: Result in this study literature search, 21 articles were found that matched the search. 5 articles were found that met the inclusion criteria. The telehealth interventions found were 4 interventions through telenursing that could significantly reduce stress, anxiety and depression in perioperative patients. Conclusion: Telehealth, especially telenursing, can reduce stress reactions, anxiety, and depression in perioperative patients and helping patients feel more prepared and less anxious. Keywords: Psychological Disorder; Perioperative; Telehealth; Telenursing.   Pendahuluan: Pasien yang menjalani pembedahan sering mengalami stres dan kecemasan, yang dapat meningkatkan komplikasi dan menghambat pemulihan. Manajemen faktor psikologis yang efektif adalah kunci untuk meningkatkan hasil. Kecemasan sebelum operasi berkorelasi terbalik dengan jumlah informasi yang diterima pasien, tetapi dukungan pribadi yang mudah diakses masih terbatas. Tujuan: Untuk mengetahui bukti yang ada mengenai praktik telehealth, khususnya telenursing pada pasien perioperatif. Metode: Tinjauan literatur dengan pendekatan kajian cepat. Strategi dalam tinjauan literatur ini adalah dengan PCC yang digunakan untuk mengembangkan pertanyaan-pertanyaan pemandu: Populasi (P): pasien bedah; Konsep (C): telehealth; Konteks (C): hasil pada periode perioperatif. Pencarian studi dilakukan dengan 3 database yaitu Pubmed, EBSCO, Proquest dan Mesin Pencari Google Scholar. Hasil: Hasil dari pencarian literatur penelitian ini, ditemukan 21 artikel yang sesuai dengan pencarian. Ditemukan 5 artikel yang memenuhi kriteria inklusi. Intervensi telehealth yang ditemukan sebanyak 4 intervensi melalui telenursing yang secara signifikan dapat menurunkan stres, kecemasan dan depresi pada pasien perioperatif. Simpulan: Telehealth khususnya telenursing dapat menurunkan reaksi stress, kecemasan, dan depresi pada pasien perioperatif. Sehingga membantu pasien merasa lebih siap dan tidak terlalu cemas. Kata Kunci: Gangguan Psikologis; Perioperatif; Telehealth; Telenursing.